Prevalence and Characteristics of Posttraumatic Nightmares in War- and Conflict-Affected Students - Schultz JH; Forsberg JT; Harb G; Alisic E (Dove Medical Press, 2021)
Jon-Håkon Schultz,1 June Thorvaldsen Forsberg,1 Gerlinde Harb,1,2 Eva Alisic3 1Department of Education, UiT, The Arctic University of Norway, Tromsø, Norway; 2Philadelphia VA Medical Center, Philadelphia, PA, USA; 3University of Melbourne, Melbourne, AustraliaCorrespondence: Jon-Håkon SchultzDepartment of Education, UiT, The Arctic University of Norway, PO Box 6050 Langnes, Tromsø, 9037, NorwayEmail j.h.schultz@uit.noIntroduction: Recurrent nightmares, frequently associated with traumatic experiences, may impair quality of life and daily functioning. However, there have been few studies of posttraumatic nightmares occurring among children and youth, in particular for trauma-exposed populations in conflict zones.Methods: Using two quantitative data sets, this study investigates the prevalence and characteristics of recurrent nightmares among conflict-exposed young people in the Gaza Strip (N = 300) and examines the characteristics of posttraumatic nightmares and their association with academic functioning among treatment-seeking students in Gaza (N = 1093).Results: Among 300 students (10– 12 years old) who lived in the ongoing conflict area in Gaza, nightmares were often mentioned, with 56% reporting recurrent nightmares with an average weekly frequency of 4.20 nights in the past week (SD = 1.94) and a mean duration of 2.48 years (SD = 2.01). Similarly, the large sample of 1093 students (6– 17 years of age) who sought help for nightmares and sleep disturbance reported recurrent traumatic nightmares on average 4.57 nights per week, with an average duration of 2.82 years. Their self-reported academic functioning was negatively affected by whether they experienced nightmares but was not associated with nightmare frequency or intensity.Discussion: Given the high prevalence of nightmares and the relation between nightmares and academic functioning, students in conflict-affected areas appear to be a particularly vulnerable group. This study proposes screening and treating conflict-affected students for recurrent ...